The exception from the rule of annexation of ownership in French law - عبد, مثنى محمد; جواد, علي كاظم (Journal of Legal Sciences, 2019)
The owner and possessor may meet in one person, thus who have these property they have its fruit. But in sometimes the owner is different than possessor, this happen in case the original owner succeeds in recovering his property or right. About that the legislations differed on the determination the person who deserves the fruits and whether the possessor is bona fide or mala fide. This paper is focused on the idea of the excluded from the rule of possession of the thing. And the applications of the rule (acquisition by possession) that belong to modern Roman law also the standpoint of Iraqi law.